THE IMPORTANCE OF LANGUAGE IN THE TEACHINGS OF MATHEMATICS ABSTRACT - Claudia Mireya Sarmiento; John Jairo Garzón Delgadillo (DIALÉCTICA, 2025)
Education is a value, and therefore, the goal is to acquire skills, customs, attitudes and knowledge that assist people in the choice, commitment, decision, application and connection with values. The task is to create an experience of values ​​so that students can develop skills and competencies that help social development. Mathematics is very important for society in terms of motivation, level differences, cognitive abilities, subject preparation, teaching methods, and student qualities. In the mathematical learning process, students face difficulties such as lack of fundamental knowledge, lack of knowledge of why or how the procedures, lack of motivation, lack of attention and concentration, lack of link with the real environment and believing that what they have learned is not useful or will not be useful in the future. In this same order of ideas, as Mendoza (2022) points out, mathematics has a language that is well-known throughout the world that simplifies communication in this area of ​​knowledge. Most teachers are interested in understanding its meaning and look for strategies to share the contents of the program to be developed well. It is important to know how language works in mathematics education and understand its codes written in different languages, such as verbal, symbolic or graphic. Hence the need to study language in the teaching of mathematics with the intention of promoting a better educational process for students and being able to communicate correctly in their daily lives and in mathematical fields.